2006
DOI: 10.1007/s10750-005-0983-x
|View full text |Cite
|
Sign up to set email alerts
|

Organic Sediment Nutrient Concentrations and their Relationship with the Hydrological Connectivity of Floodplain Waters (River Havel, NE Germany)

Abstract: Investigations on large canalised rivers, for example the Danube, have shown that transported particulate matter, which is typically inorganic, is predominantly deposited in waters near the river's main channel. This investigation deals with the lower section of the River Havel (NE Germany), a canalised lowland river with a very flat floodplain. This river is highly polluted by nutrients from urban areas (Berlin) and a long chain of river lakes produces high concentrations of phytoplankton. Due to the high pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…The bottom of the river was composed of fine sand. The shallow water benthos samples were collected with an 80-cm 2 Wolnomiejski grab and from the central deeper water with a 225-cm 2 Ekman-Birge grab. Four grabs were collected for each sample at each site.…”
Section: Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…The bottom of the river was composed of fine sand. The shallow water benthos samples were collected with an 80-cm 2 Wolnomiejski grab and from the central deeper water with a 225-cm 2 Ekman-Birge grab. Four grabs were collected for each sample at each site.…”
Section: Samplingmentioning
confidence: 99%
“…These differences refer to attribute such as the stage of ecological succession. Authors (e.g., [1][2][3]) point to the importance of hydrological connectivity between the river channel and an oxbow lake, as a key process in water-mediated transfer of energy, sediment, organic matter, and organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Focussing on organic carbon (TOC) and nitrogen (TN), deposition during overbank floods is an important ecosystem function which provides important benefits as water quality enhancement or mitigation of greenhouse effect (Johnston, 1991;Day et al, 2004;Verhoeven et al, 2006, IPCC, 2007. At the reach scale, TOC and TN exchange between the main channel and its adjacent floodplain plays a key role in the ecological functioning (Junk, 1999;Robertson et al, 1999;Tockner et al, 1999;Tockner at al., 2000;Thoms, 2003;Knosche, 2006;Preiner et al, 2008). Previous research has shown how human-induced changes at the basin and reach scale have decreased the potential of riverine floodplains to act as sediment-associated nutrient sinks (Noe and Hupp, 2005;Owens et al, 2005;Pierce and King, 2008;Cabezas et al, 2009;Cabezas and Comin, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The reason for the differences at site 3 may result from great amount of nutrition and plankton and landscape geometry from narrow stream channel (at site 2) to wide lake body with slower velocity of water flow (at site 3). Knösche (2006) found that the sediments from impounded river sections and from mouth sections of backwaters were characterised by a high proportion of particles from 0.1 to 0.5 mm size fractions, and sediments from distal sections of backwaters and of oxbow lakes tended to exhibit high element ratios with much higher variability, so these results were interpreted as a spatially limited impact of the river on the floodplain water sediments.…”
Section: Discussionmentioning
confidence: 97%
“…Connectivity of lakes and rivers, especially some urban lakes, were separated from each other because of the reconstructive activities of human such as enclosing lakes for aquaculture or impoldering lakes for building (Aoyagui and Bonecker, 2004;Cottenie and De Meester, 2003;Knösche, 2006). These obstructed lakes were usually eutrophicated for the input of sewage water, industrial wastewater or aquaculture water (Daniel et al, 1998;Correll, 1998).…”
Section: Introductionmentioning
confidence: 99%